Excimer and exciplex formation in a pair of bright phosphorescent isomers constructed from Cu3(pyrazolate)3 and Cu3I3 coordination luminophores - Zhan, Shun-Ze; Li, Mian; Zhou, Xiao-Ping; Li, Dan; Ng, Seik Weng (Royal Society of Chemistry, 2011)
Reported herein are a pair of supramolecular pseudo-isomers, namely, (Cu 3I 3)(Cu 3L 3) 2· H 2O (1) and (Cu 3I 3)(Cu 3L 3) 2 (2) (L = 3-(4-pyridyl)-5-isobutyl-pyrazolate), both of which incorporate Cu 3Pz 3 (Pz = pyrazolate) and Cu 3I 3 clusters as luminophores. The two complexes show distinct yellow (570 nm) and orange (638 nm) emissions, which are ascribed to the formation of the excimer and exciplex involving the same or different copper(i)-cluster-based luminophores. © 2011 The Royal Society of Chemistry.